Cash and COVID-19: The impact of the second wave in Canada - Heng Chen; Walter Engert; Marie-Hélène Felt; Kim P. Huynh; Gradon Nicholls; Daneal O'Habib; Hui Zhu (Bank of Canada, 2021)
We use consumer surveys conducted in April, July and November 2020 to study how the COVID-19 pandemic affected the demand for cash and the use of various methods of payment. Continuing from Chen et al. (2020, 2021), we use data from the Bank Note Distribution System (BNDS) to track how the amount of cash in circulation changed throughout 2020. The November 2020 survey included a three-day payment diary. We compare this diary with similar diaries from 2009, 2013 and 2017 to study long-term trends in cash use and payment methods.
Keywords: C; C1; C12; C9; E; E4; O; O5; O54; 330; Bank notes; Central bank research; Coronavirus disease (COVID-19); Digital currencies and fintech; Econometric and statistical methods